Contribution of shell petroleum development company (SPDC) agricultural extension programme to farmers in Oil producing areas of Delta State, Nigeria (2012)
The strained relationship between Shell Petroleum Development Company (SPDC) and host communities led SPDC to embark on agricultural extension services programme. Based on this, the study examined the contribution of this programme to farmers in the oil producing areas of Delta State. Simple random sampling technique was used to select four agricultural zones out of eleven zones based on SPDC structure. Proportionate sampling technique was used to select 122 respondents. Data collection was done through interview schedule which were subjected to descriptive and inferential statistics. Findings show that 53.3% of the respondents were within age range of 45 and 54 years, majority (76.7%) were male, 74.2% were married while 65.0% had one form of education or the other. All the farmers were aware of SPDC agricultural extension programme and 57.5% of the farmers participated in training and dissemination of information. Majority (85.8%) benefited from cassava stems, 85.8% pineapple suckers and 85.0% plantain suckers. Low benefit was recorded on tractor services (15.0%) and fishing net (21.7%). Farmers’ attitude towards SPDC agricultural programme was generally favourable. There is a significant relationship between sex (χ2; 27.928, p≤0.000), education (χ2; 24.150; p≤0.000) and contribution of SPDC agricultural programme. There was also a significant relationship between awareness (r =0.268; p≤0.003), participation (r= 0.252; p≤0.005) and the contribution of SPDC agricultural programme. Extension contact should be increased and farmers should be encouraged to form into groups in order to enhance their access to other inputs such as tractor.